The performance improvement of look-alike sound-alike drug pre-dispensing - Manutchanok Jongprasithporn; Wichai Sunkarat; Thanakorn Homsai; Teppakorn Sittiwanchai; Nantakrit Yodpijit (My University, 2018)
Medical dispensing errors are common and classic human errors in the hospitals. Look-alike, Sound-alike (LASA) drug is one of the main issues in pre-dispensing and dispensing processes. The data in this study were observed from one middle size hospital in Thailand. In 2017, there were two months that the medication errors KPI (0.065 and 0.061) were greater than the accepted error threshold (0.06). The SBAR (Situation, Background, Assessment, and Recommendation) solution and HOSxP software were applied for three months in the pre-dispensing process to reduce the medical dispensing errors. The results showed that the medication errors KPI (0.04, 0.03, and 0.02, respectively) were reduced dramatically. Therefore, implementation of the SBAR and HOSxP software is recommended as a fast and easy solution for medical dispensing errors.
Keywords: Medication error; Patient Safety and Medication Errors